Buying Time. The Delayed Crisis of Democratic Capitalism - Andrei Vernikov (Journal of Economic Sociology, 2019)
The outstanding German economic sociologist Wolfgang Streeck analyzes sources for recent fiscal, tax and economic crises, considering them as parts of the long-lasting neoliberal transformation of post-war capitalism, which started in the 1970s. Addressing the proposed crisis theories, the author discusses the subsequent contradictions and conflicts between states, governments, voters and capitalistic interests—a process of shifting the main attention from taxation through debt to budget consolidation within the European system of states. At the end of the study, he considers some perspectives on how social economic stability can be achieved again. The Journal of Economic Sociology has published some excerpts from the first chapter, “From Legitimation Crisis to Fiscal Crisis,” in which the author briefly reviews the interconnections between the financial crisis, the crisis of the tax system, and the crisis of growth. The author explains why the stratagem of these interconnections refers to an impossible riddle for any anti-crisis management as well as for politicians. Finally, the author tries to find an answer to the question of why crisis theories of the 1970s, having claimed that a legitimation crisis was coming, turned out to be unprepared to face the social trends which rejected all their predictions.